Nonequilibrium quench dynamics of hard-core bosons in quasiperiodic lattices. (29th November 2017) - Wang, Xiaohui; Tong, Peiqing
Abstract: The nonequilibrium dynamics of hard-core bosons (HCBs) in Fibonacci and generalized Fibonacci lattices following a sudden quench are studied in this paper. We numerically calculate the time evolution of one-body observables, such as the on-site density, the momentum distribution function and the occupation of the natural orbitals. It is found that in Fibonacci lattices the observables relax to time-independent values after the quenches. Moreover, after relaxation the generalized Gibbs ensemble (GGE) provides a good description for the on-site density, while GGE fails to describe the momentum distribution function and the occupation of the natural orbitals. These results are similar to those of HCBs in the localized regime of the Aubry-André model. We also studied the dynamics of HCBs in generalized Fibonacci lattices, and found that the relaxation dynamics and the resulting states after relaxation are similar to those in Fibonacci lattices.